Simulation Study On The Effect Of Rear-Wing Spoiler On The Open Aerodynamic Performance Of Sedan Vehicle - Nawam, Muhammad Zaid; Mohd Rosli, Mohd Afzanizam; Rosli, Nor Azwar Syahila (Penerbit Akademia Baru, 2018)
There is a fact that the design of the vehicle affects 11% of fuel to overcome the drag force on a high-speed driving. The relatively high value of fuel consumption had urged the engineers in the field to improve the aerodynamics aspect of the vehicle. Furthermore, the shape of the vehicle especially sedan type has greatly affected by the lift force. Undesirable high value of lift force on an automotive vehicle could cause lack of stability and safety of the vehicle. In this study, the improvisation of the aerodynamic characteristics of a vehicle only is discussed in term of rear-wing spoiler design. There are four spoiler designs proposed, analyzed and compared to each other. The drag and lift coefficient value of the vehicle with an attached spoiler and the pressure and velocity distribution are evaluated in determining the best spoiler design. The flow characteristics were analyzed using ANSYS FLUENT®. The CFD technique used is validated by using the Ahmed body as a benchmark. It shows a good agreement which is less than 10% percentage difference. Besides, a grid convergence study is also conducted to test the mesh resolution and examine the turbulence model uncertainties. All generic car and spoiler are created in CATIA®. The base car model is attached with various spoiler designs and tested to gather its data and result. The analysis conducted shows that there is an increment in the drag coefficient of the car of 47.20% when attached with a spoiler. However, the lift coefficient value shows a tremendous declination from 0.03957 to -0.16254. The result of this study show that an attached spoiler could increase the drag coefficient and decrease the lift coefficient of a car. The best spoiler should have a least increment in the drag coefficient and considerable decrement in the lift coefficient.